2006
DOI: 10.1192/pb.30.2.51
|View full text |Cite
|
Sign up to set email alerts
|

Achieving evidence-based prescribing practice in an adult community mental health service

Abstract: Aims and MethodPrescribing in everyday practice frequently deviates from evidence-based guidelines. Previous work compared practice in a community mental health service with evidence-based guidelines and identified factors related to suboptimal prescribing. This study reports the impact of a multifaceted intervention on prescribing practice. A Prescribing Practice Quality (PPQ) score was generated from six key aspects of prescribing at initial assessment and again 1 year later after an intervention to reduce s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…We have previously investigated factors associated with six aspects of psychotropic prescribing (Meagher & Moran, 2003) and studied the impact of a multidisciplinary intervention on practices at 1-year (Moran et al, 2006) and 2-year (Raju & Meagher, 2005) followup. This work indicated that sub-optimal prescribing practices (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously investigated factors associated with six aspects of psychotropic prescribing (Meagher & Moran, 2003) and studied the impact of a multidisciplinary intervention on practices at 1-year (Moran et al, 2006) and 2-year (Raju & Meagher, 2005) followup. This work indicated that sub-optimal prescribing practices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We documented six aspects of sub-optimal psychotropic prescribing rated as present (1) or absent (0) to produce a Prescribing Practice Quality (PPQ) score (Box 1), with higher scores reflecting less optimal practice. Previous work identifying determinants of sub-optimal prescribing and the impact of a multidisciplinary intervention on practice has described the PPQ (including item definitions) and the multicomponent intervention in detail (Meagher & Moran, 2003;Raju & Meagher, 2005;Moran et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…The reduction of benzodiazepine use has been a specific target within the St Anne's service for many years, [27][28][29] such that the documented rate in this study may be lower than elsewhere. However, similar to others, 30 we have found that for a small percentage of individuals maintenance use of benzodiazepines persists despite our best efforts to manage with other approaches.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…As a consequence, there may be a disproportionate awareness among clinicians of off-label prescribing in this service. [27][28][29] In addition, the inclusion of clinical ratings is a valuable aspect of this work but the cross-sectional design of the study limits the interpretation of HoNOS scores such that they may not be causally related to prescribing practice. Future work addressing the clinical and economic effectiveness of offlabel prescribing can further illuminate this issue.…”
Section: Limitationsmentioning
confidence: 99%
“…10 Although such guidance is intended to support treatment decisions in the NHS, much evidence exists to suggest that prescribing patterns in routine practice often fall short of guideline standards, including prescribing of psychotropic medications. 11 The impact of evidence from NICE and other similar organisations is dependent not only upon the availability of synthesised evidence, but also the accessibility of this evidence and indeed the attitudes of prescribing clinicians. As Towse & Wells highlighted some 15 years ago, cost-effective prescribing 'requires decision makers to believe that such information is relevant'.…”
Section: Accessibility Of Cost-effectiveness Evidencementioning
confidence: 99%